Big Nate: here goes nothing (Big Nate, ,, 2012)
"Nate's not only the star of his own comic strip--he's the star goalie of his school soccer team! Will Nate defend his goal and save the day? Or will Jefferson Middle School win...again?"--P. [4] of cover.

Booked (Crossover (Alexander: Graphic novels), 2, 1, 2022)
Twelve-year-old Nick loves soccer and hates books, but soon learns the power of words as he wrestles with problems at home, stands up to a bully, and tries to impress the girl of his dreams.

Soccer longshot (Sports Illustrated kids graphic novels, ,, 2012)
Matty is the captain of the local soccer club, the Strikers, but he needs a girl named Lola and a group of streetballers to teach him to play with flare and intensity.

Big Nate: here goes nothing (Big Nate comix, 2, 1, 2012)
"Nate's not only the star of his own comic strip--he's the star goalie of his school soccer team! Will Nate defend his goal and save the day? Or will Jefferson Middle School win ... again?"--Page 4 of cover.

Big Nate : game on!: game on! (Big Nate (Andrews McMeel Pub.), , 1, 2013)
"To sixth-grader Nate Wright, life is one big game. So when he suits up for any sport, he does it with an unmistakable swagger. From fine-tuning his trash-talking skills on the basketball court to his cocky 'tude in the soccer goal, Nate can be a bigger challenge to his teammates than their opponents."--P. [4] of cover.

The breakaways (First Second, 2019)
When a popular student encourages her to join the soccer team, Faith signs up even though she has never played the game and learns about loyalty and friendship.

Sports Illustrated Kids graphic novels: Spotlight soccer (Sports Illustrated kids. Graphic novels, , 1, 2015)
Thirteen-year-old Franco dreams of playing professional soccer, but the team in his new school is terrible, and nobody on the team, including the coach, seems to care--Franco has always been a pass-first, team-first player, but persuading this bunch ball-hogs to play the right way may be more than he can handle.

Manga math mysteries: #2,The hundred-dollar robber :a mystery with money (Manga math mysteries, , 1, 2010)
Someone has stolen money from the soccer team's car-wash earnings, and the students from Sifu Faiza's Kung Fu School must set aside their feud with the soccer players to figure out how much money was stolen and by whom.